Organic goat farming: Best way forward to farmers livelihood - Waiz, Hina Ashraf; Gautam, Lokesh (Indian Farming, 2020)
Organic goat production can improve animal welfare, protect the environment, and sustain satisfactory rural lifestyles. The future of organic goat production is to continue sorting out alternatives that are environmentally friendly, human health conscientious and animal kind. Understanding organic goat farming from economic, ecological, and animal welfare views can increase the probability of success. Goat farmers who want to get into organic goat production should learn everything they can about organic certification under the national laws. While executing this farming, farmers have time to think through and create their required Organic System Plan, talk with someone who can help them to get organic certification, start thinking through policies and procedures to be implemented, and develop a good record keeping system. If the aforesaid methods will be adopted, it will surely help a farmer to achieve a higher price for milk, meat and dairy products.